La objetividad y neutralidad de la información en la red: el tratamiento del Diario.es, ABC.es y El País.com en el juicio contra «La Manada» - Egr. Cintia LIARTE MARÍN,Dra. Elena BANDRÉS GOLDÁRAZ (Fonseca, Journal of Communication, 2023)
Spanish society has suffered a real unrest after the judicial process on the members of «La Manada», the nickname used for the five young men deemed guilty of sexual assault on an 18-year-old woman by the Navarra Court, in the San Fermin Festivals in 2016. Not onlythe trial but also the judgement has created a social movement against the judicial system on account of the court believing the sex offenders rather than the victim, according to the opinion expressed in social networks. This article focuses on the media treatment,independence, objectivity and neutrality, made by three mass media mentioned on the title as well as the coverage and reaction to the process which prove that the judgement and its consequences have meant a before and an after in the idea of sexual violence against women.